Introduction - Kousouris, Dimitris (The Historical Review/La Revue Historique, 2025)
This introduction examines the historical and cultural context in which Frangochiotika – that is, texts in the Greek vernacular written and/or printed in Latin script – were produced in the Ottoman Levant from the seventeenth to the early twentieth century. These texts served as vital tools for education and religious outreach, and as means of communication for various administrative and societal purposes. By exploring the complex dynamics of digraphia in the multilingual societies of the Eastern Mediterranean, the author traces how these publications reflect broader cultural, political and confessional interactions in the region. Furthermore, after revisiting previous scholarly efforts to catalogue and analyse these materials, he argues that a more systematic study of them will contribute to a deeper understanding of identity formation and linguistic practices in the plural and contested space of the Eastern Mediterranean.